Project-Based Learning in Teaching EFL Writing In SMP Negeri 1 Tembuku: An Analysis of the Effect on The 5 Dimensions of Writing - Wardani, Ni Komang Sri; Artini, Luh Putu; Ramendra, Dewa Putu (Journal of Education Research and Evaluation, 2021)
This study aimed at finding out the effect of Project-Based Learning on students’ writing skill of grade 9 at SMPN 1 Tembuku. This study empplied embedded mixed method design, in which the quantitative data were considered as the main data. The data were collected through guided interview, observation, open-ended questionnaire, and writing test. Paired-sample t-test was used to analyze whether or not there is a significant difference in students’  writing skill before and after being taught using PBL, and Manova  was used to To analyze how project-based learning affected students’ writing skill in term of content, organization, structure, vocabulary, and mechanic. While the qualitative data were analyzed descriptively.The result showed that Project-Based Learning has significant effect on students’ English writing skill and it also affected the students’ writing skill in term of  content, organization, structure, vocabulary, and mechanic (sig. = .000 < α = . 05). Project-Based Learning also revealed potentially promotes students’ critical thinking, creativity, collaborative work, and enhances teacher’s satisfaction in teaching . In general, it can be concluded that Project-Based Learning significantly improves students’ writing skill of the 9 grade students.